Management Evaluation of Regional Government Implementation Report (LPPD) in Waropen Regency, Papua Province in 2022 - Padang, Sylva; Masengi, Evi Elvira; Sendow, Recky H.E (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to evaluate the management of the preparation of the Regional Government Implementation Report in Waropen Regency, Papua Province in 2022. This research uses descriptive qualitative method. The data collection techniques used are observation, interviews, and literature studies. Local governments have special rights and authorities to regulate and manage their own government affairs in the regions through the principles of regional autonomy and assistance tasks given by the central government. Local governments need to report on governance based on the Regional Development Work Plan (RKPD). The results of the study stated that the lack of communication and coordination between the leaders of the Regional Apparatus Organization (OPD) and the Regional Secretariat caused a lack of synchronization in the context of collecting data and information on Key Performance Indicators (KPI) between performance and reality in the field of public services. The low accountability of human resources that led to the results of PAD in 2022 which contributed 0.46% of the total realization of regional revenue.